IDENTIFICATION OF SOIL CORROSION POTENTIAL FOR PLANNING IN THE GAS PIPELINE CATHODIC PROTECTION SYSTEM - Agus Solehudin; Enda Permana; Haipan Salam (Program Studi Fisika Universitas Negeri Jakarta, 2022)
Research has been carried out to map and identify the potential for soil corrosion for the planning of cathodic gas pipeline protection systems. The research location is located in Cimanggis - Bitung, West Java, which is located at coordinates 6o19'00